The Interplay of Reflective and Experimental Spaces in Interrupting and Reorienting Routine Dynamics - Bucher, Silke; Langley, Ann (Organization Science, 2016)
When organization members strive to radically change routines, they face a puzzle: How can they bring about change in performances when these are guided by pre-existing ideas on how to perform the routine, that are themselves recursively reproduced? Drawing on insights from longitudinal case studies of two initiatives to change patient processes in hospitals, this paper suggests that two types of “spaces”—bounded social settings characterized by social, physical, temporal, and symbolic boundaries—are important mechanisms through which actors engage in deliberate efforts to alter both performances (performative aspect) and abstract understandings (ostensive aspect) of a given routine. Specifically, whereas reflective spaces are set apart by social, physical, and temporal boundaries and involve interactions that are geared toward developing novel conceptualizations of a routine, experimental spaces enable the integration of new actions into routine performances by locating them within the original routine, while establishing symbolic and temporal boundaries that signal the provisional and localized nature of experimental performances. As both types of spaces contribute to achieving change in complementary ways, they need to be enacted iteratively in relation to each other. The study offers a model of intentional routine change that articulates the role of spaces in interrupting and reorienting their recursive dynamics.